Sensory and motor nerve conduction velocity in long-term diphenylhydantoin therapy - José H. Xavier de Castro; Mario L. Acosta; Roberto E. P. Sica; Nelly Guercio (Arquivos de Neuro-Psiquiatria)
Eleven epileptic patients under long-term DPH therapeutical doses were studied and the obtained results allow us to postulate that DPH, when is administrated for long periods, can produce damage of the peripheral nerve by involvement of the sensory and motor fibres in a similar degree.